Analisis Pengambilan Keputusan Pembelian Fashion Involvement terhadap Impulse Buying di Masa Pandemi - Acep Samsudin; Rusdi Hidayat; Shinta Kezia Apriliani; Bebyzanna Bella Faumara; Anindya Sekar Purnomo; Nabilla Rahma Maharsany (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the influence of Fashion involvement in buying decisions on Impulse Buying Through the Positive Emotions of Teenagers during the Covid-19 pandemic. In making this journal using the method of literature study. In compiling this journal, the author uses various journals with the discussion of each journal still related to being a reference material in making this journal. The results of the study show that fashion involvement and positive emotion have an impact on impulse buying. This means that fashion involvement has a positive influence on impulse buying behavior with fashion involvement playing an important role because it has an impact on consumer decisions and positive emotion also has a positive influence on customer desires to make unplanned purchases, so that it has a big impact on consumer desires to make impulse buying. Keywords: Fashion involvement, positive emotion, impulse buying.